A Survey Tool, Retrenchment Blues and a Career Alternatives Program - Renner, K. Edward (Canadian Journal of Higher Education, 1991)
Two-thirds of the faculty of Canadian universities will reach the traditional retirement age of 65 between the years 2000 to 2010. As a result there will be little academic or financial flexibility for at least another decade. A questionnaire is presented as a tool for measuring the personal and professional characteristics of this age group with respect to three considerations: (1) their level of career satisfaction, (2) their interest in a career alternatives program, and (3) their plans to retire either before or by the age of 65 or to continue to work after 65 if mandatory retirement is abolished. A significant proportion of academic faculty are no longer finding satisfaction in their academic work and would consider an alternative career if that were feasible. Those who are not interested in leaving academic life early tend to be happy and productive. A career alternatives program could be an effective way to begin the renewal process within higher education now, not after the year 2000.